Tū Kaha: He Mōhio ki ngā Māori o Te Kōmaoa Waewae (Stand Strong: A Qualitative Study of Māori With Venous Leg Ulcers in Aotearoa New Zealand) - Kidd, J; Wharakura, MK; Laking, G; McGregor, D; Dobson, R; Jull, A (SAGE Publications, 2024)
Venous leg ulcers have impact on people’s lives far beyond that of a skin lesion but these impacts have not been explored from an Indigenous perspective. We used a Māori-centered narrative approach to interview 13 Māori in Aotearoa New Zealand with venous leg ulcers. Data analysis was informed by a reflexive thematic approach and four themes were identified: Ko waewae ahau (I wear the leg); Ngā mea hōhā (annoying things); Ka tangi te ngākau (heartfelt grief); and Mamae (pain, sore, hurt). Recognizing patients’ expertise in their condition, the inclusion of whānau (family) in care planning and provision, while providing consistent advice and resource access, would all enhance the experience of venous ulcer management. Training in venous leg ulcer care needs to move beyond a focus on the leg and toward a more holistic approach that encompasses a broader understanding of patient experiences and cultural contexts when managing venous ulcers.
Keywords: Indigenous population; Māori; New Zealand; experience; qualitative research; venous leg ulcers; 52 Psychology; 5203 Clinical and Health Psychology; 5201 Applied and Developmental Psychology; Pain Research; 7.1 Individual care needs; Skin; 3 Good Health and Well Being; 1302 Curriculum and Pedagogy; 1701 Psychology; 1702 Cognitive Sciences; Public Health; 5201 Applied and developmental psychology; 5203 Clinical and health psychology; Humans; New Zealand; Male; Qualitative Research; Female; Middle Aged; Varicose Ulcer; Aged; Adult; Leg Ulcer; Interviews as Topic; Maori People; Humans; Varicose Ulcer; Leg Ulcer; Qualitative Research; Adult; Aged; Middle Aged; New Zealand; Female; Male; Interviews as Topic; Maori People; Humans; New Zealand; Male; Qualitative Research; Female; Middle Aged; Varicose Ulcer; Aged; Adult; Leg Ulcer; Interviews as Topic; Maori People